The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsinfecdis.9b00066
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Membrane Structural Remodeling Increases Resistance to Antimicrobial Peptide LL-37

Abstract: Gram-negative bacteria are protected from their environment by an outer membrane that is primarily composed of lipopolysaccharides (LPSs). Under stress, pathogenic serotypes of Salmonella enterica remodel their LPSs through the PhoPQ two-component regulatory system that increases resistance to both conventional antibiotics and antimicrobial peptides (AMPs). Acquired resistance to AMPs is contrary to the established narrative that AMPs circumvent bacterial resistance by targeting the general chemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…The upregulation of phoP in Δ1538 corroborated with a previous report on phoP upregulation in the mutant of ortholog STM14_1829 [19]. We further investigated the expression of PhoP-regulated genes in Δ1538, as these have been previously reported in stress resistance by Salmonella [34,36,37]. Genes encoding Mg 2+ transporters mgtA, mgtB, and mgtC showed 23.73fold, 320.77-fold, and 216.48-fold downregulation in Δ1538 compared to WT, respectively (Figure 2(c)).…”
Section: Sen1538 Promotes Resistance To Stressorssupporting
confidence: 87%
“…The upregulation of phoP in Δ1538 corroborated with a previous report on phoP upregulation in the mutant of ortholog STM14_1829 [19]. We further investigated the expression of PhoP-regulated genes in Δ1538, as these have been previously reported in stress resistance by Salmonella [34,36,37]. Genes encoding Mg 2+ transporters mgtA, mgtB, and mgtC showed 23.73fold, 320.77-fold, and 216.48-fold downregulation in Δ1538 compared to WT, respectively (Figure 2(c)).…”
Section: Sen1538 Promotes Resistance To Stressorssupporting
confidence: 87%
“…7,8 LPS modification processes, such as the PhoPQ system depicted in Figure 1, reduce this charge through adornment of the lipid A phosphate groups. [9][10][11] In S. enterica, these modifications are activated by a variety of environmental stimuli, such as a low concentration of divalent cations, 12,13 acidic conditions, 14,15 hyperosmotic stress, 16 or antimicrobial peptide presence, 17,18 indicating that modifications may confer a survival advantage in such conditions. Additionally, previous simulations have shown that the presence of aminoarabinose disrupts the cation network, allowing direct inter-lipid hydrogen bonding to instead stabilize the leaflet and potentially reducing the reliance on divalent cations for stability.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the resistance mechanisms can be seen in Figure 1. Most commonly, resistance to LL-37 occurs as a result of structural changes to the bacterial membranes [7], including modifications to the cell membrane [20], cell surface charge [9,21], capsule [25], and efflux pumps [26]. Furthermore, resistance may develop through the upregulation and downregulation of specific genes [25,27], and through the resulting alterations to cellular processes and secretions, including metabolism [19], the expression of virulence factors [28], proteases [12,27,29], and outer membrane proteins (OMP) and vesicles [12,27,29].…”
Section: Resistancementioning
confidence: 99%